Cardiac Dysrhythmias Associated With Substitutive Use of Loperamide: A Systematic Review. (January 2019) - Riaz, Irbaz Bin; Khan, Muhammad Shahzeb; Kamal, Muhammad Umar; Sipra, Qurat-ul-Ain Riaz; Riaz, Anum; Zahid, Umar; Bhattacharjee, Sandipan
Abstract : Background: Recently, several deaths secondary to cardiac arrhythmias have been reported in association with substitutive use of loperamide. Therefore, we conducted a systematic review of all reported cases to overview the epidemiologic patterns and clinical outcomes to better elucidate loperamide-induced cardiac complications. Areas of Uncertainty: Association between substitutive use of loperamide and cardiac arrhythmias. Data Sources: A comprehensive literature search was conducted across 6 databases using variety of keywords to identify all reports of cardiac side effects associated with loperamide abuse. Only original case reports of cardiac toxicity or cardiac arrhythmias after loperamide abuse or overuse were included. Data were extracted by 2 authors independently using a structured template from the selected reports. Quality assessment of the reports was performed by using a high-quality evaluation tool. Results: Thirteen reports describing 19 cases were included in our review. Except for coronary artery spasm in one case, cardiac arrhythmias were the major reported cardiac adverse event. The average age of patients was 31 years with majority being men (79%). The most common presentation was syncope (63%). All cases were reported in US except for 1 case. Three patients were concomitantly taking cimetidine, which is known to cause inhibition of CYP3A4 and CYP2C8 leading to increased levels of loperamide. Thirteen of 19 patients were successfully treated and discharged in a stable condition. Conclusions: Our results indicate that measures such as restricting over-the-counter availability of loperamide and increasing awareness regarding loperamide's toxicity are imperative to prevent deaths associated with loperamide abuse.